Prototipe Aplikasi Penghitung Matrik Berbasis Java - Muhammad Rizqi Nur; Dwi Rolliawati (Systemic: Information System and Informatics Journal, 2018)
Matrix is one among math subjects which are considered hard. Matrix is considered hard mainly because there are so many calculations needed to be done. Because of the same reason, finding faults in the calculations is also hard, which makes the learning process that mainly consists of exercises harder. To overcome that, a matrix calculator software which can show the calculation steps was developed. The development produced prototype model which has five main features, which are elementary row operation helper, basic matrix operation calculator, matrix form calculator, matrix determinant calculator using Laplace expansion, and a solver for linear equations using Cramer’s rule. The application had been tested with black box testing for its functionality which shows that every feature was working properly. However, this application has not been tested for its effectivity, so it is still considered a prototype.